217 The end-tidal and arterial carbon dioxide gradient in serious traumatic brain injury after pre-hospital emergency anaesthesia: a retrospective observational study. Issue 12 (23rd November 2020) - Price, James; Sandbach, Daniel; Ercole, Ari; Wilson, Alastair; Barnard, Ed
Abstract : Aims/Objectives/Background: In the United Kingdom (UK), 20% of patients with severe traumatic brain injury (TBI) receive pre-hospital emergency anaesthesia (PHEA). Current guidance recommends an end-tidal carbon dioxide (ETCO2 ) of 4.0–4.5kPa to achieve a low-normal arterial partial pressure of CO2 (PaCO2 ), and reduce secondary brain injury. This recommendation assumes a 0.5kPa ETCO2 -PaCO2 gradient. However, the gradient in the acute phase of TBI is unknown. Our primary aim was to report the ETCO2 -PaCO2 gradient of TBI patients at hospital arrival. Methods/Design: A retrospective cohort study of adult patients with serious TBI, who received a PHEA by a pre-hospital critical care team in the East of England between 1st April 2015 to 31st December 2017. Linear regression was performed to test for correlation and reported as R-squared (R 2 ). A Bland-Altman plot was used to test for paired ETCO2 and PaCO2 agreement and reported with 95% confidence intervals (95%CI). ETCO2 -PaCO2 gradient data were compared with a two-tailed, unpaired, t-test. Results/Conclusions: 107 patients were eligible for inclusion. Sixty-seven patients did not receive a PaCO2 sample within 30 minutes of hospital arrival and were therefore excluded. Forty patients had complete data and were included in the final analysis; per protocol. The mean ETCO2 -PaCO2 gradient was 1.7 (±1.0) kPa, with only moderate correlation of ETCO2 and PaCO2 at hospital arrival (R 2 =0.23, p =0.002). The Bland-Altman bias was 1.7 (95%CI 1.4–2.0) kPa with upper and lower limits of agreement of 3.6 (95%CI 3.0–4.1) kPa and -0.2 (95%CI -0.8–0.3) kPa respectively. There was no significant gradient correlation in patients with a co-existing serious thoracic injury (R 2 =0.13, p =0.10), and this cohort had a larger ETCO2 -PaCO2 gradient, 2.0 (±1.1) kPa, p =0.01. Patients who underwent pre-hospital arterial blood sampling had an arrival PaCO2 of 4.7 (±0.2) kPa. Lower ETCO2 targets than previously recommended may be safe and appropriate. The use of pre-hospital PaCO2 measurement is advocated.